PROFILING IN BORDER CONTROL SERVICES: A MONGOLIAN PERSPECTIVE - Bolortungalag Getsel (International Journal of Innovative Technologies in Social Science, 2025)
Profiling at border control services involves using a set of criteria based on observable factors like travel patterns, behavior, and document details to identify individuals who may pose potential security risks. This approach allows border officials to focus their scrutiny on those considered more likely to be involved in illegal activities such as smuggling, human trafficking, or terrorism while facilitating smooth passage for low-risk travelers. Implementation occurs through a combination of data analysis, observation, and questioning techniques by trained border officers, often utilizing specialized software to flag potential concerns based on collected information. This article explores the use of profiling techniques in border control services, focusing on Mongolia’s border security context. It discusses the historical evolution of profiling from criminal psychology to its current role in identifying security threats. The research highlights the importance of profiling as a complement to technological solutions in addressing human factors in border security. It compares traditional Mongolian identification methods with modern profiling techniques and identifies challenges faced by Mongolian Border Security Checkpoint officers. The study suggests the need for formal profiling training programs, specialized curricula, and dedicated profiling teams with diverse expertise to improve border security operations.